Two-year outcomes of methadone maintenance therapy at a clinic in Malaysia - Musa, Ramli; Abu Bakar, Ahmad Zafri; Khan, Umeed Ali (Sage Publications, Inc, 2011)
Background. The commencement of methadone maintenance therapy (MMT) in 2005 represents a quantum leap in the management of heroin dependence in Malaysia. Objective. To examine the 2-year outcomes of this modality in the treatment of heroin dependence with respect to the quality of life (QOL), heroin abstinence, and rate of employment among heroin dependants attending the Tengku Ampuan Afzan Hospital (HTAA) MMT clinic. Method. This was an experimental study in which the second QOL assessment was conducted 2 years after treatment initiation. Results. A total of 172 patients enrolled at the point of entry to the MMT program. The authors examined 107 patients who remained in the program 2 years later (62.6% retention rate). A paired t test demonstrated sigsnificant improvements in all 4 domains of QOL (physical, psychological, social relationships, and environment; P < .001). The most marked improvement was noted in the psychological domain. Conclusion. The MMT program at HTAA is effective in improving the QOL among heroin dependants.